Hydrothermal Synthesis and Crystal Structure of [4,4’]Bipyridinyl Silver Nitrate Ion - Zhu, M.; Song, H.L. (Asian Journal of Chemistry, 2015)
One new silver compound Ag(NO3), thiophene-2,5-dicarboxylic acid and [4,4']bipyridinyl (bpp) has been successfully synthesized. The compound has been characterized by X-ray single-crystal diffraction, compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.